Audit of head injury management in Accident and Emergency at two hospitals: implications for NICE CT guidelines - Tennant Alan; Kent Ruth M; Miller Lucy (BMC, 2004)
Abstract Background The National Institute for Clinical Excellence (NICE) has produced guidelines on the early management of head injury. This study audits the process of the management of patients with head injury presenting at Accident and Emergency (A&E) departments and examines the impact upon resources of introducing NICE guidelines for eligibility of a CT scan. Methods A retrospective audit of consecutive patients of any age, presenting at A&E with a complaint of head injury during one month in two northern District General Hospitals forming part of a single NHS Trust. Results 419 patients presented with a median age of 15.5 years, and 61% were male. 58% had a Glasgow Coma Score (GCS) recorded and 33 (8%) were admitted. Only four of the ten indicators for a CT scan were routinely assessed, but data were complete for only one (age), and largely absent for another (vomiting). Using just three (incomplete) indicators showed a likely 4 fold increase in the need for a CT scan. Conclusions The majority of patients who present with a head injury to Accident and Emergency departments are discharged home. Current assessment processes and associated data collection routines do not provide the information necessary to implement NICE guidelines for CT brain scans. The development of such clinical audit systems in a busy A&E department is likely to require considerable investment in technology and/or staff. The resource implications for radiology are likely to be substantial.